Pesquisa soro-epidemiológica para arbovírus em macaco-prego-galego (Cebus flavius) de vida livre no estado da Paraíba e em macaco-prego (Cebus libidinosus) de cativeiro no nordeste do Brasil - LAROQUE, Plautino de Oliveira (2013)
This study describes the first investigation of antibodies for arboviruses on non-human primates from the New World in five states of the northeast of Brazil. From March 2008 to September 2010 blood serum samples were collected of 31 free living galician capuchin monkeys (Cebus flavius) from Paraíba and of a 100 capuchin monkeys (Cebus libidinosus) of the Sorting Center for Wild Animals (CETAS) from the states of Alagoas, Paraíba, Pernambuco, Piauí and Rio Grande do Norte. The Haemagglutination-Inhibition Test (HI) was utilized and four hemagglutinating units of 19 arboviruses antigen and serum, diluted from 1:20, were used. The antigens were prepared by the sucrose-acetone extraction method and the monkeys’ serum were treated with acetone and adsorbed with goose blood cells. Among the blood sera examined, all galician capuchin monkeys were negative and 46/100 (46%) of capuchin monkeys presented anti-arbovirus anticorpses. The arbovirus seropositivity were 29% for MAYV, 28% for OROV, 26% for ILHV, 19% for SLV, 15% for EEEV, 12% for ROCV, 9% for WEEV, 9% for MUCV and 2% for YFV . From these samples, 15 presented monotypic reaction to ILHV (n=4), MAYV (n=6), SLEV (n=1), ROCV (n=2), OROV (n=1) e MUCV (n=1), without the isolation from the viral agents. These results suggested that there were an intense circulation of arboviruses in the studied population of capuchin monkeys in CETAS.